Neurotic Tendencies Through Emotional Characterics In Character's Personality In Creative Works: (Kecenderungan Neurotisme melalui Karekteristik Emosional dalam Personaliti Watak Karya Kreatif) (Malay Literature, 2021)
The integration of character and characterization in the production of a novel is an important element to ensure the narration of the novel can be accepted by readers. This research aims to identify the existence of emotional characteristics through neurotic tendencies in the formation of a character's personality in creative works. The problem of character development and characterization always arises in literary works due to the dissimilarity between the fictional and real human life. Emotional characteristics in neurotic tendencies are related to human emotions in writing and presentation. Hence, the novel Andai Itu Takdirnya by Siti Rosmizah Ismail, which has received good reviews in the website Goodreads.com and has become a phenomenon among readers of novels in Malaysia, was chosen as the research material. To conduct this research, the main characters in the novel were first identified through the narrative. Then, every main character was classified based on neurotic tendencies in their emotional characteristics. Next, the data was analysed by using the content analysis method, through combining the Big Five Personality Theory and the Five-Part Model by Padesky (1986) and modifying it for character and characterization. Based on the analysis, the development of a character's personality, influenced by the characteristics stated in the Five-Part Model (environment, thought, feelings, actions, and response), has to be applied to characters created by the author. The results from this research can provide guidance for writers to develop character personality in order to produce creative worksof high value, to have a positive impact on readers.Keywords: Personality, language, Big Five Personality Theory, adolescents, neuroticism